THE RELATIONSHIP BETWEEN DYSMENORRHEA INTENSITY AND LEARNING ACTIVITIES IN ADOLESCENT FEMALE STUDENT AT SMPN 4 KALANGANYAR - Agis Prastiani; Alif Nurul Rosyidah; Osep Yasier Almunsiri (Poltekkes Kemenkes Banten, 2026)
Background: Dysmenorrhea is pain or abdominal cramps that occur during menstruation. Dysmenorrhea can have an impact on adolescent girls as it can disrupt daily activities, especially learning activities at school, due to the intensity of menstrual pain experienced. Objective: The purpose of this study was to determine the relationship between dysmenorrhea intensity and learning activities in adolescent female students at SMPN 4 Kalanganyar. Method: This type of research uses a quantitative method with a cross-sectional design. The population in this study was female students at SMPN 4 Kalanganyar, totaling 95 people. The sampling technique used was total sampling, where the sample size was equal to the population. The data analysis used was the chi-square test. Result:The chi-square test results showed a p-value of 0.000 (p <0.05). Conclusion: These results indicate that there is a relationship between dysmenorrhea intensity and learning activities in adolescent female students at SMPN 4 Kalanganyar